The Geographical and Institutional Proximity of Scientific Collaboration Networks - Frank Van Oort; Roderik Ponds; Koen Frenken (European Regional Science Association (ERSA), 2006)
The geography of innovation has established itself as a central subject in economic geography. Geographical proximity to firms and organizations like universities is supposed to have a positive effect on a firms' innovative performance. One of the reasons causing these positive agglomeration effects is the fact that collaboration is eased by geographical proximity. Although the role of proximity for collaboration is a well researched theme with regard to innovation, less is known about the role of proximity in scientific collaboration and how this affects the probability and nature of networking among research institutions. This is surprising given the fact that collaboration in science has become a central policy issue. In this paper we set out a number of theoretical considerations about the role of geography for innovation and see whether these apply for science as well. The empirical part will focus on the geography of collaboration in scientific knowledge production, testing the hypothesis that collaboration between different kinds of organizations is geographically more localized than collaboration between the same kinds of organizations due to institutional or organizational proximity. Besides this we will analyze the importance of spatial proximity for various forms of collaboration (such as university-university and university-firm collaboration) using the concept of the gravity model. Finally we will look at the spatial structure of these collaboration networks using insights from social network methodology. Based on co-publications, central nodes of collaborative interaction and network structures are analysed over time. On the network-level we conclude on differences in the fields of life- and physical sciences and on differences on the type of relations according to university-firm, university-university and university-governmental institution linkages. On the regional level we conclude on the centrality and spatial extent of scientific collaboration hubs over time
Keywords: 330